Techniques to increase silage stability and starch availability and the effects of heat stress abatement systems on reducing heat load in dairy cattle - Johnson, Jared R. (Kansas State University, 2017)
Four studies were conducted that focused either on silage quality parameters or heat abatement systems to improve cow comfort. Study 1 evaluated the effects of treating whole-plant corn at harvest with a dual-purpose commercial silage inoculant containing Lactobacillus buchneri and Lactococcus lactis O224 on fermentation and aerobic stability of corn silage through 32 d of ensiling. Inoculating silage to be fed after minimal storage time (≤ 32 d post-harvest) had no effect (P > 0.05) on the chemical composition, fermentation variables, aerobic stability or rise in temperature post-harvest. Study 2 was designed to develop a berry processing score (BPS) for sorghum silage as well as evaluate the change in starch digestibility as the level of berry processing increased. A method to evaluate the level of processing in sorghum silage was successfully developed by measuring the percent of starch passing through a 1.7 mm screen. This provides the industry with a standardized method to measure the level of processing in sorghum silage. As BPS increased from 26.28 to 55.05 ± 0.04%, 7-h in situ starch digestibility increased from 50.54 to 82.07 ± 4.94% for unprocessed and heavily processed sorghum silage, respectively (R² = 0.43). By processing sorghum silage during harvest and measuring the extent of processing, sorghum silage starch digestibility can be enhanced and may serve as a viable alternative to corn silage in the diet of lactating dairy cows in areas of the country where corn silage is a high-risk forage crop due to lack of water. Study 3 evaluated the effects of 2 heat stress abatement systems on barn temperature, micro-environmental temperature, core body temperature (CBT), respiration rate, rear udder temperature, and lying time in lactating dairy cows. The systems evaluated were: direct cooling via feedline soakers and fans, or evaporative cooling via a fan and fog system. The evaporative cooling system was effective (P = 0.04) in reducing respiration rates (52.0 vs. 57.9 ± 2.2 breaths per min; P < 0.01) and rear udder temperatures (33.2 vs. 34.5 ± 0.3ºC; P < 0.01), and increased daily lying time (11.8 vs. 10.8 ± 0.3 h/d; P < 0.01) due to differences in barn THI and airflow. No treatment differences (P = 0.79) were detected for CBT, likely due to cooler ambient conditions during the study. Study 4 assessed the effects of the same evaporative and direct cooling systems as in Study 2 but were applied in the holding area prior to afternoon milking, where effects on CBT and micro-environmental temperature in lactating dairy cows were measured in addition to water usage by each system. No significant differences (P > 0.05) between direct cooling and evaporative cooling were detected for micro-environmental THI. However, the evaporative cooling system reduced the consumption of water in the holding area while maintaining CBT < 39.0ºC. Future research should be conducted under greater ambient THI to determine if an evaporative cooling system is able to maintain CBT < 39.0ºC, while also comparing CBT and water usage to a soaker system in the holding area.
Keywords: Silage; Inoculant; Aerobic stability; Starch digestibility; Heat stress; Evaporative cooling